PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS GAME FROGGY JUMPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SUMBER DAYA ALAM DI KELAS IV SD BIREUEN - Maulida; Khairunnisak; Lissa Zikriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students' learning outcomes, teacher and student activities, and student responses through the implementation of the Problem-Based Learning (PBL) model assisted by the digital game media Froggy Jumps on the topic of Natural Resources in the 4th-grade class of SD IT Muhammadiyah Bireuen. The type of research used is Classroom Action Research (CAR) with 18 student subjects. The results showed a significant increase in all aspects measured, where teacher activity increased from 80.5% in cycle I to 95.8% in cycle II, and student activity increased from 68.4% to 92.1%. Furthermore, students' cognitive learning outcomes experienced a drastic improvement, with the class average score rising from 62.5 to 84.3 and the percentage of classical mastery increasing from 22.22% in cycle I to 88.89% in cycle II, alongside very positive student responses toward the use of this interactive media. In conclusion, the Problem-Based Learning model assisted by the Froggy Jumps digital game is effective in improving science learning outcomes (IPAS) regarding Natural Resources in elementary schools.